Financial Technology and Its Impact on Modern Financial Systems: Opportunities, Challenges, and Future Prospects - Indah Kusuma; Rendara Kumala (Universitas Nurul Jadid, 2025)
The rapid development of digital technology has significantly transformed the global financial landscape. Financial Technology (FinTech) has emerged as a disruptive innovation that integrates financial services with advanced digital technologies, enabling more efficient, accessible, and inclusive financial systems. This study aims to examine the role of financial technology in transforming financial services, identify the opportunities created by FinTech innovation, and analyze the challenges associated with its implementation. Using a qualitative approach based on literature review, this research analyzes various academic publications, institutional reports, and policy documents related to financial technology development. The findings indicate that FinTech contributes to financial inclusion, improves operational efficiency in financial institutions, and promotes innovative financial products and services. However, the expansion of FinTech also presents several challenges, including regulatory uncertainty, cybersecurity risks, and issues related to consumer protection. The study concludes that FinTech will continue to play a crucial role in shaping the future of financial systems, provided that appropriate regulatory frameworks and technological governance mechanisms are implemented to ensure sustainable development.